Synthesis of Manganese Oxide – Magnetite (Fe3O4) for The Degradation of Methylene Blue - Ramadhanti, Aulia Rizki; Awaluddin, Amir; Nurhayati, Nurhayati; Siregar, Sri Hilma (Photon: Jurnal Sain dan Kesehatan, 2025)
Methylene blue is a dye that is challenging to break down in aquatic environments. A promising approach to degrade methylene blue involves using metal oxide-based materials. Magnetite (Fe₃O₄) is beneficial for easy separation after catalytic reactions, while manganese oxide is effective in oxidation processes. Combining manganese oxide and magnetite can create materials with synergistic properties that improve the degradation of methylene blue through photocatalytic mechanisms or modified Fenton reactions. The development of manganese-magnetite oxide (Fe₃O₄) composites offers a potential solution for efficient, eco-friendly, and reusable catalysts. This study aims to investigate the synthesis of manganese-magnetite oxide and its performance in methylene blue degradation as an innovative solution to water pollution. The MnOx-Fe₃O₄ composite was successfully synthesized using the hydrothermal method at 110°C for 6 hours. XRD results show that increasing Fe₃O₄ concentration enhances the Fe₃O₄ peak, while the Hausmanite peak disappears, overlapping with the Fe₃O₄ peak, as supported by SEM results. The MnOx-Fe₃O₄ composite (1:10 ratio) was most effective in degrading methylene blue, achieving 92% degradation of 100 mL of 20 ppm methylene blue with a catalyst concentration of 0.1 g and 5 mL of H₂O₂ using the Fenton method.